PRESERVATION OF MOCI TRADITION IN MANTU POCI RITUAL IN TEGAL SOCIETY (PERSPECTIVE REVIEW OF LITERARY ANTHROPOLOGY) - Elen Inderasari; Dwi Rahmawati; Dwi Kurniasih (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Local traditions or culture characterize an interesting area to be researched. There is a lot of oral literature that developed in Tegal City, one of which is the moci tradition. Moci is a term for drinking tea that is brewed in a pot made of clay. The purpose of this study is to describe the preservation of the moci tradition in the Tegal community and the ritual ceremony of the mantu pot in terms of the perspective of literary anthropology. This type of qualitative descriptive research is used with the perspective of a literary anthropology approach. The types of data and sources of primary research data are documentation of the Mantu Poci Tradition procession and direct interviews from respondents such as writers and humanists from Tegal, village elders, community leaders, educators, and people who have been fully involved. Secondary data were obtained from library materials in the form of written sources related to the ritual of the mantu teapot. Data collection with events, in-depth interviews, and documentation related to the ritual of the mantu teapot. The technique of checking the validity of the data in this study uses triangulation with data sources and method triangulation. The data analysis used the Spradley model with the study of literary anthropology. The results of the research on the preservation of the moci tradition in the form of socialization show that the Mantu Poci ritual has three stages of preparation, implementation, and closing. In addition to the mantu poci tradition as an effort to preserve the moci tradition, there are also several efforts to preserve the moci tradition through written works in the form of novels and books, songs, drama performances, and become mandatory dishes in all major activities in Tegal City.